Pariwisata dan pembangunan ekonomi : Bali sebagai kasus - Erawan, I Nyoman, 1948- (Denpasar : Upada Sastra, 1994)
Economic significance of tourist development in Bali Province.
Revision of the author's thesis (doctoral--Universitas Gadjah Mada, 1987).
Includes bibliographical references (p. 189-196) and index.
Keywords: Tourism -- Indonesia -- Bali (Province); Bali (Indonesia : Province) -- Economic conditions